PERENCANAAN GEOMETRIK,TEBAL PERKERASAN PADA RUNWAY,TAXIWAY DAN APRON BANDARA SAMARINDA BARU - SENO AJI, ARI (KURVA S JURNAL MAHASISWA, 2014)
Airport is the area of land and water with a limit - a certain extent being used as aircraft landing and taking off, up and down passengers, loading and unloading facilities equipped with safety and aviation security. With the airport then to the area - an area that is difficult to reach by land transportation as well as a separate area by sea will be easy to reach with relatively short travel time.Samarinda is the most crowded cities in the Province of East Kalimantan, where the need for transportation to the area - the area in East Kalimantan province requires a relatively long time with ground transportation and still the poor condition of infrastructure makes the city of Samarindamust make BandaraSamarindaBaru lieu TemindungAirport Capacity and regions which are no longer feasible due to runway Temindung Airport that often flooded when it rains as well as densely populated position.In planning service BandaraSamarindaBArurefer to the rulesby the Department of Transportation Section Air referring to regulations - FAA regulations (Ferderal Aviation Administration) an institution owned airlines USA (United States Of America) as well as the ICAO (International Civil Aviation Organzation) institutions flight under the auspices of the United Nations (UN - Nation).From the planning service New Samarinda airport, planned for the Airbus A 320-200 can land at the airport and the runway length is 3,000 m with a thickness of 66 cmfor runway,58 cm for taxiway and 30 cm for apron . And for the apron is 194.643 m².